Importance of Orbital Interactions in Determining Electronic Band Structures of Organo-Lead Iodide - Kim, Jongseob; Lee, Seung-Cheol; Lee, Sung-Hoon; Hong, Ki-Ha (American Chemical Society, 2015)
Organic-inorganic perovskites are promising materials for improving the efficiency of solar cells, but there are still uncovered issues on the understanding of their electronic band structures. Using first-principles calculations, we investigate the electronic band features of organo-lead iodide perovskites and present the efficient model to predict the band gap variation based on the orbital interaction scheme. The orbital interaction between Pb and I atoms can be controlled through the structural modification such as the change in lattice constant and the deviation of I atoms from cubic symmetry sites. The increase of the lattice constant and the positional distortion of I atoms from the cubic symmetry sites lead to the increase of the band gap. With our findings, puzzling band gap variation behaviors in previous experiments and simulations can be understood, and we suggest a pathway to precisely control their band gap. Our study can serve as the design rule for band gap engineering for various kinds of organic-inorganic hybrid perovskites.
Keywords: INORGANIC HALIDE PEROVSKITES; HYBRID SOLAR-CELLS; OPTICAL-PROPERTIES; TOTAL-ENERGY; LOW-COST; EFFICIENCY; 1ST-PRINCIPLES; EMERGENCE; TRANSPORT; INTERPLAY